The Influence of FOMO and Impulsive Buying on Students' Personal Financial Management Moderated by Self Control - Hasanah, Safrina; Sundari, Siti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to examine the relationship between the fear of missing out (FOMO) and impulsive buying, with self control as a moderating variable. Â Methodology: This study employs a quantitative method with the population being undergraduate students of state universities in Surabaya. Using a purposive sampling technique, 100 samples were obtained. The SmartPLS 4.0 application was used as a data analysis technique. Results The results of the study indicate that low fear of missing out and impulsive buying have a positive impact on students' personal financial management. Self-control can moderate the impact of fear of missing out and impulsive buying on students' personal financial management. Findings: This study highlights that state university students in Surabaya are able to control themselves from the influence of FOMO and impulsive buying. Novelty and originality: This study contributes to the development of knowledge about personal financial management of students influenced by fomo and impulsive buying, especially among Gen Z of State Universities in Surabaya. Conclusion: The lower the level of FOMO and impulsive buying, the better the student's personal financial management. and high self-control, able to control the influence of FOMO and impulsive buying. Type of Paper: Reasearch Paper